Hubungan Antara Self-Care Dan Kontrol Glikemik (Hba1c) Pada Pasien Dengan Diabetes Melitus Tipe 2 - Wirda Wirda; Andi Masyita Irwan; Ariyanti Saleh Saleh (Jurnal Keperawatan Muhammadiyah, 2019)
AbstractIntroduction: Diabets Melitus (DM) is one of the degenerative diseases with chronic properties which are the main causes of cardiovascular disease, blindness, kidney failure and lower extremity amputation. The prevalence of type 2 DM will increase in low and middle income countries if there is no effective management and strategy for the treatment. Self-care DM plays a role to reduce the risk or slow the progression of complications from type 2 diabetes. DM requires HbA1c examination to assess long-term glycemic status and reduce complications. The purpose of this literature study is to review the literature on the relationship between Self-care and glycemic control in type 2 DM patients. Methods: Literature search is done through searching scientific publications by using several databases, such as Google Scholar, PubMed with the keywords "Diabates Mellitus", "Self-care" and "" glycemic control "and getting 278 relevant articles. Articles included in the final analysis that meet inclusion criteria.Results: Self-care has a direct effect on glycemic control in patients with DM, so self-care is highly recommended to reduce complicationsConclusion: Self-care has a direct effect on glycemic control so self-care is recommended for DM patients to reduce their risk and slow down the complications of type 2 DM.